LoRa IoT Network for Instant Forest Fire Detection and Alert System - R. Anand; P. Monisha; T. Nathiya; S.Karthik (Scientific Research, New Technologies and Applications Vol. 7, 2024)
The present study highlights about LoRa IoT Network for Instant Forest Fire Detection and Alert Systems. Around the world, forest fires have become a serious problem since they damage homes, wild animals, and trees while also contaminating the air with a high Air Quality Index. Natural and man-made disasters alike were rocking the globe. Tragedies like forest fires are one kind of environmental impact. Once started in the depths of the forest, the fire quickly spreads throughout the whole region, consuming all it touches. The hothouse effect and climatic changes are two effects of similar devastation. For detecting numerous environmental characteristics that may approach the threshold level during a fire-based mishap, this suggested system uses an Arduino and a variety of sensors. The Internet of Things (IoT) will bring new intelligence and efficiency to long-standing technologies such as home automation, control systems, and wireless sensor networks. Here, the temperature and smoke level of two primary factors are regularly monitored. Smoke is detected using the gas sensor MQ6, which measures and detects carbon-based gases. The Ds18b21 wire-based temperature sensor can detect smoke since smoking produces CO2. Furthermore, a PIR sensor is used to identify any human movement. One Arduino analogue pin is connected to the analogue temperature and gas sensors. At the location of the node and hub, the fire uses Long Range Communication (LoRa) to alert the appropriate Tamil Nadu Forest Department. The detecting system uses very little electricity and is powered by solar panels. LoRa can send data over larger distances of up to 15 km. To monitor and save these characteristics, an online interface is also established. Extensive field testing has demonstrated the system’s effectiveness in real-world outdoor environments, where it continuously collects and transmits vital sensor data related to temperature, humidity, and other critical forest conditions. This data can be used to monitor potential fire hazards and inform timely responses, thereby enhancing forest management and safety protocols.